2011
DOI: 10.2337/db10-0830
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fat Depot–Specific Mechanisms Underlie Resistance to Visceral Obesity and Inflammation in 11β-Hydroxysteroid Dehydrogenase Type 1–Deficient Mice

Abstract: OBJECTIVEThe study objective was to determine the key early mechanisms underlying the beneficial redistribution, function, and inflammatory profile of adipose tissue in 11β-hydroxysteroid dehydrogenase type 1 knockout (11β-HSD1−/−) mice fed a high-fat (HF) diet.RESEARCH DESIGN AND METHODSBy focusing on the earliest divergence in visceral adiposity, subcutaneous and visceral fat depots from 11β-HSD1−/− and C57Bl/6J control mice fed an HF diet for 4 weeks were used for comparative microarray analysis of gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 56 publications
7
65
2
Order By: Relevance
“…This indicates a possible feed-forward loop-inflammation stimulating the HPA axis to secrete glucocorticoids, both of which induce C/EBP␤ in turn increasing 11␤-HSD1, further amplifying local glucocorticoid signaling and shaping the trajectory of an inflammatory response via pro-resolution macrophage polarization (600). A recent intriguing twist is added by the discovery that the C/EBP␤ posttranslational isoforms, liver inhibitory protein (LIP) and liver activator protein (LAP), play distinct physiological roles (647,763) and oppose each other in mediating 11␤-HSD1 regulation in adipose tissue by high-fat diet (190), itself linked to adipose inflammation (750).…”
Section: A Gene Structure and Controlmentioning
confidence: 99%
“…This indicates a possible feed-forward loop-inflammation stimulating the HPA axis to secrete glucocorticoids, both of which induce C/EBP␤ in turn increasing 11␤-HSD1, further amplifying local glucocorticoid signaling and shaping the trajectory of an inflammatory response via pro-resolution macrophage polarization (600). A recent intriguing twist is added by the discovery that the C/EBP␤ posttranslational isoforms, liver inhibitory protein (LIP) and liver activator protein (LAP), play distinct physiological roles (647,763) and oppose each other in mediating 11␤-HSD1 regulation in adipose tissue by high-fat diet (190), itself linked to adipose inflammation (750).…”
Section: A Gene Structure and Controlmentioning
confidence: 99%
“…These studies demonstrated that systemic and/or local GC excess is associated with reduced adipose tissue insulin signaling and significant glucose and lipid homeostasis imbalance [10,11,16,28] . The alterations in insulin signaling pathway include reduced adipose tissue IRS-1 Tyr and PKB Ser/Thr phosphorylation [10,11,16] . By blocking/reducing the 11β-HSD-1 enzyme activity with pharmacological [28] genetic (knockout) [11] or molecular (knockdown) [16] tools, obese mice made by prolonged GC exposure or high-fat diet become partially prevented from the glucose and lipid imbalance, suggesting a negative impact of elevated local GC abundance for adequate adipose tissue biology.…”
Section: Research Highlightmentioning
confidence: 99%
“…In models of visceral obesity by prolonged exposure to corticosterone [10,16] or diet-induced obesity [11,28] , it is common to observe an increase of GC availability in the visceral adipose tissue as a consequence of 11β-HSD-1 upregulation (the isoform that catalyzes the intracellular activation of GCs) [16,28] . These studies demonstrated that systemic and/or local GC excess is associated with reduced adipose tissue insulin signaling and significant glucose and lipid homeostasis imbalance [10,11,16,28] . The alterations in insulin signaling pathway include reduced adipose tissue IRS-1 Tyr and PKB Ser/Thr phosphorylation [10,11,16] .…”
Section: Research Highlightmentioning
confidence: 99%
See 2 more Smart Citations